Local currency and its social aspects - Szóka, Károly (Acta Scientiarum Socialium, 2013)
Local currency and its social aspects Local currency and similar initiatives can be found in many places of the world. These can be either self-help, administrative systems (for example Time Dollars, Ithaca Hours) or emissions of a money substitute’s local currency (for example WIR, Chiemgauer, Urstromtaler, Kékfrank). The local currency works similar to the vouchers but it is transferable and has secondary circulation. It complements the trading of national currency but it does not want to replace it. Its role is to connect economic and non-economic stakeholders; protect the local economy and as well it can be used like an anti-crisis resource. The difficulty of the system’s administration is to set up an organization which operates it. The costs of marketing and public relations are high; it is also hard to convince the entrepreneurs of joining it; there is no governmental guarantee and the early mistrust is also significant. The local currency can only be operated by regional co-operation and for this the collaboration of the local governments, entrepreneurs and individuals is needed.
Keywords: local currency; substitutes for money; local economy; economic stimulus